Moisture-dependent pupation of the invasive thrips Chaetanaphothrips orchidii: implications for its management - Juncá-Morales, Carolina; Catalán, José; Gómez-Martínez, María A.; Intrigliolo, Diego S.; Tena, Alejandro (Wiley, 2025)
BACKGROUND: Chaetanaphothrips orchidii is an invasive thrips of tropical origin that was detected in 2016 in Spanish citrus, where it can damage up to 70% of the fruit. Pupation site and emergence rates are key biological traits for thrips management that are unknown for C. orchidii. Here, we determined the pupation site and period of C. orchidii in citrus and evaluated the effect of soil moisture on adult emergence. RESULTS: A two-year field study showed that C. orchidii pupated in the soil from May to December in commercial citrus orchards. Chaetanaphothrips orchidii emergence was very low compared to other harmful thrips species in citrus. Using D/E traps, we demonstrated that the thrips emerged mainly from wet areas near drip irrigation emitters during the summer, and its emergence was strongly related to the soil water content. A laboratory experiment confirmed that C. orchidii did not emerge at RH below 70%, and its emergence peaked at 97% RH. CONCLUSIONS: Our results have important implications for the sustainable management of C. orchidii because soil moisture is very low in Mediterranean citrus during summer, except in areas near drip irrigation emitters. Therefore, these and other potential high-humidity areas should be considered crucial targets to manage this pest in citrus during summer, reducing cost and labor.